MANAGEMENT OF THE BATUR GEOPARK AS GEOLOGICAL CONSERVATION BASIS - Hadian, Sapari Dwi; Suganda, Bombom Rachmat; Sunarie, Cecep Yandri; Barkah, Mochamad Nursiyam; W M Iskandarsyah, Teuku Yan; Bulqiah Ulfa, Ratu; Krishna Yuliawati, Ayu; Arfiansyah, Kurnia (Journal of Geological Sciences and Applied Geology, 2022)
The Batur Caldera is located in Kintamani District, Bangli Regency, Bali Province. The coordinates are 8 0 14.30' South Latitude, 115 0 22.30 East Longitude. The closest city distance is Bangli. The Batur Caldera contains the Batur Volcano and to the right is Lake Batur. Around it, in accordance with the beliefs of the local community, there are many temples, such as Besakih Temple and Pasar Agung Temple.Indonesia's success in making the Batur Caldera a Geopark recognized by UNESCO, thanks to the hard work of the Bangli Bali Regent/Pemda, Kemenparekraf, ESDM Geology Agency. In an effort to promote themselves and improve the quality of Batur Caldera geopark tourist destinations.Indonesia's wealth consisting of flora, fauna, cultural diversity, is a tourism asset that Indonesia already has that is able to realize love for national diversity as well as national unity. In addition, geological heritage (geoheritage) and sustainable geological diversity are the beginning of a geological park (geopark) towards nature-based tourism activities (geotourism). Geopark is the protection of cultural and natural heritage by emphasizing the potential between socio-economic and cultural development and the preservation of the natural environment. Geotourism as an earth heritage contains geological sites, which can produce science, scarcity, beauty, and education. Referring to conservation, education, and local economic growth.In realizing Geotourism in Indonesia, it is necessary to have the role of Tourism Stakeholders, namely a group of tourism actors who are responsible for implementing tourism that is responsible for preserving nature and is sustainable, including the Central Government, Regional Government, Private sector, and the Indonesian Tourism Promotion Agency.The government is supervised by the Ministry of Tourism and Creative Economy which is handed over to the Culture and Tourism Office in each region in the development of infrastructure, policies, regulations and promotions. In addition, the Geology Agency, as an institution that carries out geological conservation efforts in the context of sustainable development, is planning and preparing to organize the Geotourism. Besides that, there is the role of the community, several expert institutions in their fields to empower the community to be able to participate in the geotourism industry. Keyword : Geopark, Geotourism, Stakeholders, Batur Caldera